Free-hand placement of iliac screws for spinopelvic fixation based on anatomical landmarks: technical note - Fridley, Jared (Int J Spine Surg, 2014)
BACKGROUND: The placement of iliac screws is a biomechanically sound method for the stabilization of long multi-segment lumbar constructs. Traditional techniques for the placement of iliac screws often involve either substantial iliac muscle dissection for visualization of screw trajectory based on bony landmarks, or alternatively the use of intra-operative imaging to visualize these landmarks and guide screw placement. We describe an alternative free-hand method of iliac screw placement, one that needs neither significant muscle dissection nor intra-operative imaging. METHODS: We performed this technique in 10 consecutive patients. Patient demographics, spinal pathology, post-operative complications, and screw hardware characteristics are described. RESULTS: We have successfully used this technique for the placement 20 iliac screws based on anatomic landmarks in 10 consecutive patients. There were no cortical breeches of the ileum and no penetrations into the acetabulum on post-operative imaging. There were no instances of hardware failure. Two patients developed deep vein thromboses after surgery, 1 had a pulmonary embolism. CONCLUSIONS: Based on our limited experience to date, free-hand placement of iliac screws is both easy to perform and safe for the patient. Further study and validation using this technique is warranted.